2019
DOI: 10.1136/bmjopen-2018-026591
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and applying practitioner and patient views on the implementation of a novel automated Computer-Aided Risk Score (CARS) predicting the risk of death following emergency medical admission to hospital: qualitative study

Abstract: ObjectivesThe Computer-Aided Risk Score (CARS) estimates the risk of death following emergency admission to medical wards using routinely collected vital signs and blood test data. Our aim was to elicit the views of healthcare practitioners (staff) and service users and carers (SU/C) on (1) the potential value, unintended consequences and concerns associated with CARS and practitioner views on (2) the issues to consider before embedding CARS into routine practice.SettingThis study was conducted in two National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Despite the advantages of efficiency of scale and depth of computational power, 3 , 4 , 5 concerns have been expressed by scientists, practitioners and broader publics about the systematic datafication of people's lives and their lived experiences of health and illness. 6 , 7 , 8 , 9 , 10 It is unclear whether AI‐assisted health care always leads to better patient outcomes, whether it empowers and enables patients/service users, carers and their families, and whether patients or the public have a meaningful say over AI‐assisted processes of care or design of such systems. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of efficiency of scale and depth of computational power, 3 , 4 , 5 concerns have been expressed by scientists, practitioners and broader publics about the systematic datafication of people's lives and their lived experiences of health and illness. 6 , 7 , 8 , 9 , 10 It is unclear whether AI‐assisted health care always leads to better patient outcomes, whether it empowers and enables patients/service users, carers and their families, and whether patients or the public have a meaningful say over AI‐assisted processes of care or design of such systems. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Our approach to the development of CARM has involved a process of codesign with healthcare professionals and service users 6. Previous papers discuss the development and validation2 and the potential value, unintended consequences, concerns and predicted implementation needs6 of the CARM.…”
Section: Discussionmentioning
confidence: 99%
“…We have sought to codesign CARM with service users and carers as part of the project team as well as participants 6 9. In the study reported here, we had the input of three team members (GB, KD and JG) from the Service User and Carer Involvement in Research Group at the University of Bradford, which has been involved in the development of CARM over the last 4 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that different doctors and patients have unique preferences for the type and style of information delivery, patient similarity models will probably not replace conventional risk models, but complement them with a new variety of information that can be selectively used in the appropriate consultation context. [28].…”
Section: Discussionmentioning
confidence: 99%